Investigating manual sprout removal in stored yam: effect of tuber sizes on some physicochemical properties - Etudaiye, H.A.; Uvere, P.O.; Rees, D.; Abayomi, L.; Westby, A.; Maroya, N.G.; Ukpabi, U.J. (2020)
The study focused on manual sprout removal and effect of tuber sizes on some physicochemical properties of the stored yams. Yam variety, Ameh (Dioscorea rotundata) with different tuber sizes ≤ 0.5 Kg, 0.6-0.9 Kg and ≥ 1.0 Kg for small (SS), medium (MS) and big(BS) sizes, respectively, were used. The primary nodal complex (PNC) was removed using three methods: hand picking, half cutting and full cutting. Tubers were stored on shelves for 16 weeks in a yam storage laboratory at National Root Crops Research Institute, Umudike, Nigeria. Physicochemical parameters determined were temperature, relative humidity, sprout count, weight loss (WL), dry matter (wet basis), starch yield, amylose, reducing sugars (TRS), water absorption capacity (WAC) and bulk density (BD). Weight loss significantly (p>0.05) increased with storage. The mean dry matter (DM) across sprout removal methods showed significant difference (p>0.05), and lowest in big tubers (30.77%). DM was lowest in control and hand picking at 16 weeks. Starch yield, amylose and TRS were highest in the MS tubers. Values of MS tubers for starch, amylose and TRS were 25.88%, 13.11% and 3.11%, respectively. Starch, amylose and sugars decreased with storage. There was a significant difference (p>0.05) in starch yield, amylose and sugars across tuber size and across storage period. Mean values of tubers for manual sprout removal methods during storage on BD and WAC were significant (p>0.05) and highest in BS tubers (0.47 g/ml BD and 2.00 g/ml WAC).